A Model of Menternship for Public Organizations - Yousef Vakili; Akbar Hassanpoor; Saeed Jafarinia; Abdossamad Azizpour lindi (فرایند مدیریت و توسعه, 2023)
Purpose: Mentern is a strategy that can help organizations in the field of generational differences. Therefore, for this purpose, the end of this study is to design a model of Mentern in public organizations. Methodology: This research was conducted using the Glacerian Grounded theory. Semi-structured interview was used to collect data, and after interviewing 19 experts, theoretical saturation was obtained. The data using actual coding (open and selective coding) and theoretical coding were analyzed. Finding: The findings showed that mentoring as a core category, supportive management system, empowering human resource management, dynamic organizational structure, learning culture, suitable individual characteristics and personality of mentoring, interpersonal skills, supportive culture of society as a context and the formation of a positive attitude towards the organization, development of professional and leadership abilities, improvement of job performance, formation of cooperative climate and improvement of organizational performance were identified as outcomes. Originality/ Value: The present research has been able to provide a comprehensive model for the implementation of the mentern in public organizations by examining the characteristics of different working generations and the concepts of coaching and mentoring. Recommendations: According to the proposed model, managers are advised to distance themselves from hierarchical structures, and to use suitable people and train them to provide opportunities for the implementation of mentern in order to reduce the generation gap in public organizations.